IMPROVING ENGLISH SKILLS OF YOUTH ORGANIZATIONS IN PAMMANA VILLAGE THROUGH AUDIO-VISUAL MEDIA - Amiruddin Amiruddin; Satriani Satriani (Jurnal Abdimas Indonesia, 2021)
Pammana is a village in Kabupaten Wajo, Sulawesi Selatan, where the majority of the residents work as farmers. With a low income, parents' capacity to send their children to a higher level of education is always hampered. Based on the aforementioned circumstances, the writer and team are interested in delivering English language training for the youth organization utilizing an audio-visual medium. The goal of this program was to make the training sessions more exciting and accessible to the participants through the use of audiovisual media. This English training exercise has a positive impact on the Pammana village youth group. These favorable effects might be seen as a result of the training. The learning results of the training participants improved after only a few months of following the training procedure using the audio-visual medium. Before attending the training, the trainees thought English was a difficult language to learn; however, after attending the training utilizing audio-visual media, the trainees began to feel more at ease, and they thought learning English through audio-visual media was enjoyable.